PFOA and testis cancer in the Veneto Region (Italy) - Mario Saugo; Enrico Ioverno; Armando Olivieri; Francesco Bertola; Angela Pasinato; Alan Ducatman (BMC, 2024)
Abstract The largest documented episode of human contamination by PFOA in the world (approximately 150,000 actual residents on 1 January 2020) has occurred in Italy's Veneto Region. In this large, mostly flat plain area, a cluster of testicular cancers has also been observed. Preliminary data are reported, and the most relevant and recent recommendations regarding the health surveillance of exposed individuals are emphasized.